PERAN SERTA MASYARAKAT DESA SEMUNTAI DALAM PELAKSANAAN PROGRAM COMMUNITY DEVELOPMENT - wita, De; Zainal, Sofyan; Natalina H, Uke (JURNAL HUTAN LESTARI, 2013)
Communiy development is one of the guideline citivity concept on society and corporation have to apply it. This research aims to know the participation of sosiety at Semuntai Village on appllaying community development; to know correlations among age, education, knawledge, income, the people is preception about the mediators and cosmopolitan in applying community development in Finnantara Intiga corporation. This is a description structure interview method on 78 household and data analyzed using Chi square. The participation of people mostly different and has a high correlation to the level of education. On the other hands, level of age factor, knowledge, income, people perception on the mediators action and cosmopolitan didnt show high correlation to the participation of society in programme community development. Keyword : Participation, Community, Community Development, Semuntai